Individual Baseline Balance Assessments in a Large Sample of Incoming NCAA Division I Athletes Using a Force Plate System - Scott A. Weismiller; Robert Monaco; Jason Womack; Brandon Alderman; Carrie Esopenko; Fiona N. Conway; Kyle Brostrand; Allison Brown; Nicola L. de Souza; Jennifer F. Buckman (International Journal of Sports Physical Therapy)
# BACKGROUND Individualized baseline testing is resource and time intensive. The use of normative data to approximate changes after a suspected concussion is thus an appealing alternative. Yet, few peer-reviewed, large-sample studies are available from which to develop accurate normative averages of balance using force-plate technology.